AN OVERVIEW OF MEDICINAL VALUE OF CURCUMA SPECIES - Kanase, Vanita; Khan, Farha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Curcuma is a genus of about 100 accepted species in the family Zingiberaceae that contains such species as turmeric and Siam tulip. They are native to Southeast Asia, southern China, ISSN (Online): 2319-7064 ISSN (Online): 2319-7064 naturalized in other warm parts of the world such as Tropical Africa, Central America, Florida, and various islands of the Pacific, Indian, and Atlantic Oceans. Few known species of Curcuma with reported pharmacological activity are Curcuma longa, Curcuma aeruginosa, Curcuma pseudomontana, Curcuma aromatica, Curcuma xanthorrhiza, Curcuma zedoaria, Curcuma angustifolia. Among them, C. longa is the one species extensively studied and has ancient traditional medicinal uses. These Curcuma species have been used in traditional medicine as a household remedy for various diseases, including biliary disorders, anorexia, cough, diabetic wounds, hepatic disorders, rheumatism, and sinusitis. For the past few decades, extensive work has been done to establish the biological activities and pharmacological actions of Curcuma species and its extracts. This review article is created with an intention to give an overview on the reported research carried out on the Curcuma species such as anticancer activity, antitumor, antitubercular, antibacterial, antimicrobial, toxicity activity, and wound healing. And also, these Curcuma species can be considered as herbal medicinal plant having a plethora of research opportunities based on its traditional use and biological activity.